The Role of Socioeconomic Status, Family Resilience, and Social Support in Predicting Psychological Resilience Among Chinese Maintenance Hemodialysis Patients - Qiu, Yuan; Huang, Yingying; Wang, Yuxin; Ren, Liya; Jiang, Hao; Zhang, Liping; Dong, Chaoqun (Frontiers in Psychiatry, 2021)
Objectives: Evidence regarding the possible influence of social factors on psychological resilience among maintenance hemodialysis patients is scarce. The aim of this study was to explore the relationship among socioeconomic status, family resilience, and social support, and psychological resilience among Chinese maintenance hemodialysis patients. Methods: This cross-sectional study was conducted in the hemodialysis centers of three comprehensive hospitals in China from September to December 2020 using convenience sampling. Two hundred fifty-eight patients receiving maintenance hemodialysis were investigated using a sociodemographic questionnaire, the Chinese version of the Medical Outcomes Study-Social Support Survey (MOS-SSS), Chinese Family Resilience Assessment Scale (C-FRAS), and Chinese version of the Conner and Davidson resilience scale (CD-RISC). Results: Maintenance hemodialysis patients reported a low level of physical resilience, with a score of (58.92 ± 15.27). Hierarchical linear regression analysis showed that education level (β = 0.127, p = 0.018), maintenance of a positive outlook by the family (β = 0.269, p = 0.001), positive social interaction support from the family (β = 0.233, p = 0.002), and tangible support (β = −0.135, p = 0.037) were significantly associated with psychological resilience. Conclusion: SES, family resilience and social support may be potential predictive factors of psychological resilience. Interventions to improve the family resilience and social support may be beneficial to promote the psychological resilience of Chinese maintenance hemodialysis patients.